BELAJAR TATAP MUKA MASA PANDEMI COVID-19 PADA SEKOLAH DASAR DI KECAMATAN SEMARANG BARAT - Naufaldi Endi Rahmadanni; Eram Tunggul Pawenang (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
The SARS-CoV-2 virus that causes a worldwide pandemic has changed the learning system to online since early 2020. However, the Ministerial Decree 4 states that schools may hold face-to-face learning in 2021. The purpose of the study was to determine the preparation of elementary schools to carry out face-to-face learning. This type of research is descriptive with a population of 45 elementary schools in the district of West Semarang. The results of the study provide an overview of toilets (100%), hand washing facilities (100%), disinfection (100%), access to health services (87%), application of social distancing (10%), checking body temperature (56%), use of PPE (100%), human resources (80%), parent counseling (100%), monitoring (68%). So, it can be concluded that elementary schools are ready to learn face-to-face with an average score of 85.8%.